2023
DOI: 10.1126/sciadv.adg3715
|View full text |Cite
|
Sign up to set email alerts
|

Bioaerosols are the dominant source of warm-temperature immersion-mode INPs and drive uncertainties in INP predictability

Gavin C. Cornwell,
Christina S. McCluskey,
Thomas C. J. Hill
et al.

Abstract: Ice-nucleating particles (INPs) are rare atmospheric aerosols that initiate primary ice formation, but accurately simulating their concentrations and variability in large-scale climate models remains a challenge. Doing so requires both simulating major particle sources and parameterizing their ice nucleation (IN) efficiency. Validating and improving model predictions of INP concentrations requires measuring their concentrations delineated by particle type. We present a method to speciate INP concentrations int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 103 publications
1
10
0
Order By: Relevance
“…Our model results show that PBAP are the primary source of INP between −12°C and −20°C. This agrees with a recent observational and modelling study by Cornwell et al (2023). Overall, mineral dust (Fig.…”
Section: Simulations and Inp Evaluationsupporting
confidence: 93%
See 2 more Smart Citations
“…Our model results show that PBAP are the primary source of INP between −12°C and −20°C. This agrees with a recent observational and modelling study by Cornwell et al (2023). Overall, mineral dust (Fig.…”
Section: Simulations and Inp Evaluationsupporting
confidence: 93%
“…Reviewing experimental and modeling studies, Burrows et al (2022) summarized the level of understanding and parameterisations of INP activity of 10 particle types that could represent INP in climate models. In immersion freezing, which is the dominant mode of primary ice formation in MPC (Hande and Hoose, 2017), desert dust, marine primary organic aerosols (MPOA) and terrestrial 95 primary biological aerosol particles (PBAP) have emerged as the most relevant INP sources (McCluskey et al, 2018;Chatziparaschos et al, 2023;Spracklen and Heald, 2014;Cornwell et al, 2023). These findings align with the physical understanding that INP are often efficiently activated as cloud condensation nuclei due to internal mixing with soluble components and their large size.…”
Section: Introduction 45mentioning
confidence: 71%
See 1 more Smart Citation
“…This adds complexity to the estimation of the influence of aerosols on clouds [23][24][25]. Increasing knowledge about the characteristics of INPs will improve the accuracy of evaluating the impact of aerosols on clouds and reduce the level of uncertainty involved [18,26].…”
Section: Introductionmentioning
confidence: 99%
“…For example, mineral dust particles with large emission rates of up to 5000 Tg yr –1 are recognized as the most important INP type because of their generally effective ice nucleation ability. Previous studies have found that dust particles activate as ice crystals at temperatures above −15 °C in the immersion mode . Additionally, biological aerosols including bacteria, pollen, viruses, fungi, and phytoplankton can also act as effective INPs with freezing temperatures ranging from −3 °C for bacteria to below −38 °C for marine aerosols. Furthermore, many studies have shown the pervasive presence of ammonium sulfate and sulfuric acid particles in the upper troposphere. These particles exhibit homogeneous freezing temperatures below −38 °C, playing a significant role in the formation of cirrus clouds. …”
Section: Introductionmentioning
confidence: 99%